The silk and spices routes, exploration by sea - "Reid, Struan" (Belitha: London, 1993)
Covering the earliest Chinese explorations to the flowering of cities and civilizations along the silk and spice routes, this book concerns exploration by sea. It describes the movement of ideas, peoples, trade and cultures and includes information on artefacts and archaeological evidence.
Keywords: Asia Civilization-Book